Dehydration of AlPO4-34 studied by variable-temperature NMR, XRD and first-principles calculations. (21st December 2015) - Varlec, Jure; Krajnc, Andraž; Mazaj, Matjaž; Ristić, Alenka; Vanatalu, Kalju; Oss, Andres; Samoson, Ago; Kaučič, Venčeslav; Mali, Gregor
Abstract : Complementary techniques elucidate water–framework interactions in different states of dehydration, two of which have not been observed before. Abstract : Microporous zeolite-like aluminophosphate AlPO4 -34 is a very promising material for water-adsorption-based thermal energy storage. To obtain better understanding of the dehydration of this material, a detailed variable-temperature nuclear magnetic resonance (NMR), X-ray diffraction (XRD), and first-principles calculation study was carried out. Unlike the previous studies, this one detected three distinct phase transitions during dehydration. The fully hydrated phase of AlPO4 -34 first loses one water molecule per unit cell and transforms into the partly dehydrated phase I (space group P 1). The molecule that was expelled first is the molecule that was initially located within the double six-membered ring and was very weakly coordinated to the aluminium atom and not involved in hydrogen bonds. During the second phase transition a water molecule is expelled from each chabazite cage. The obtained partly dehydrated phase II (space group P 1̄) contains six water molecules in each chabazite cage and four water molecules coordinated to octahedral aluminium. The third transition leads to the completely dehydrated material. Structures of both partly dehydrated phases of AlPO4 -34 were determined by the Rietveld method. Variable-temperature NMR and XRD detected very different phase-transition temperatures. This was due to very different sample packing, which significantly influenced the rate of water removal. The confirmation that the two techniques observed the same phases of AlPO4 -34 was obtained by the first-principles calculations of NMR observables. Using the XRD-based structural models, the calculations predicted 31 P and 27 Al isotropic chemical shifts that agreed well with the observed ones.